Estimating the potential for habitat restoration and connectivity effects on European sturgeon (Acipenser sturio L. 1758) population rehabilitation in a lowland river – the Havel, Germany. (17th October 2014) - Gessner, J.; Zahn, S.; Jaric, I.; Wolter, C.
Summary The intention of the paper is an evaluation of the restoration potential of the Spree‐Havel River system for rheophilic and anadromous fish species. The European sturgeon Acipenser sturio was used as an indicator species in the Spree‐Havel River system, focusing on the effects of providing longitudinal passage: (Scenario 1), and two possibilities for spawning site restoration (Scenario 2 = altered flow conditions below weirs and gravel addition, and Scenario 3 = fundamental riverbed modification to create spawning habitats). To determine the effects on population development, an age‐structured population model for A. sturio was used. Targets of the study were to predict potential effects of a Havel population on the Elbe River population, as well as to assess the effects of restoration and connectivity on the fish assemblage of the Spree‐Havel system, with special reference to the goals of the EU Flora‐Fauna‐Habitat Directive and the EU Water Framework Directive. The paucity of sturgeon caught in the Spree‐Havel River system during the 19th century indicates that alterations to the river system (mill weirs, flow alterations and communal wastes input) contributed to a significant population decrease. Restoration of the river connectivity alone will have little effect on its potential to support a sturgeon population without moderate improvements to the hydro‐morphology and habitat structures (scenario 2 = restoration of 30% of the potential habitats, resulting in 30 000 m2 of spawning habitat). This approach would increase the population potential dramatically when combined with the reestablishment of longitudinal connectivity up to Neuendorf Lake, which would reopen 220 km of river passage. As a result, the sturgeon population in the river system could contribute an estimated 41% to the potential total Elbe River population. The Spree‐Havel system has an estimated support potential of between 15 400 and 42 000 juvenile fish during out‐migration from the system and 4300–11 700 spawners for an annual return. Results of the modeling study confirm that the main restrictions to reach the WFD goals are associated with the lack of hydro‐morphological and hydro‐dynamic diversity in adjacent river stretches.